Preoperative Degenerative Changes at the Tibial Sesamoid-Metatarsal Joint in Hallux Valgus: Association With Postoperative Patient-Reported Outcomes After Modified Lapidus Procedure - Sophie Kush BS; Stone R. Streeter BS; Agnes D. Cororaton Jones MS; Brett Steineman PhD; Scott J. Ellis MD; Matthew S. Conti MD (Foot & Ankle Orthopaedics, 2024)
Background: Degenerative changes at the sesamoid-metatarsal joints (SMJs) may be a source of pain following hallux valgus surgery. The aims of this study were to describe degenerative changes at the SMJs on weightbearing computed tomography (WBCT) scans and, secondarily, investigate their association with 1-year patient-reported outcome scores following a modified Lapidus procedure for hallux valgus. We hypothesized that reduced joint space in the SMJs would correlate with worse patient-reported outcomes. Methods: Fifty-seven hallux valgus patients who underwent a modified Lapidus procedure had preoperative and minimum 5-month postoperative WBCT scans, and preoperative and at least 1-year postoperative PROMIS physical function (PF), pain interference, and pain intensity scores were included. Degenerative changes at the SMJs were measured using distance mapping between the sesamoids and first metatarsal head on preoperative and postoperative WBCT scans. The minimum and average distances between the first metatarsal head and tibial sesamoid (tibial-SMJ) for each patient preoperatively and postoperatively were measured. Sesamoid station was measured on WBCT scans using a 0 to 3 grading system. Linear regression was used to investigate the correlations between minimum preoperative and postoperative tibial-SMJ distances and 1-year postoperative PROMIS scores. Results: The median minimum and average tibial-SMJ distances increased from 0.82 mm (interquartile range [IQR] 0.40-1.03 mm) and 1.62 mm (IQR 1.37-1.75 mm) preoperative to 1.09 mm (IQR 0.96-1.23 mm) and 1.73 mm (IQR 1.60-1.91 mm) postoperative (P < .001 and P < .001), respectively. In a subset of patients with complete sesamoid reduction, we found an association between preoperative minimum tibial-SMJ distance and 1-year postoperative PROMIS PF scores (coefficient 7.2, P  = .02). Conclusion: Following the modified Lapidus procedure, there was a statistically significant increase in the tibial-SMJ distance. Additionally, in patients with reduced sesamoids postoperatively, reduced preoperative tibial-SMJ distance correlated with worse PROMIS PF scores. Level of Evidence: Level IV, case series.